The StarvAnx Study-Comparison Between the Effects of Non-fasting Vs. Fasting Strategy on Surgical Outcomes, Anxiety and Pain in Patients Undergoing Cataract Surgery Under Topical Anesthesia: A Randomized, Crossover, Controlled Trial - Guerrier, Gilles; Bernabei, Federico; Giannaccare, Giuseppe; Vagge, Aldo; Bonnet, Clémence; Baillard, Christophe; Monnet, Dominique; Rothschild, Pierre-Raphaël (Frontiers in Medicine, 2022)
Background: Fasting is usually recommended in patients undergoing cataract surgery under topical anesthesia. However, starving before surgery may increase preoperative anxiety and affect surgical outcomes. It is not known which fasting or non-fasting strategy is best for cataract surgery. The aim of this study was to compare non-fasting and fasting strategy in patients undergoing cataract surgery under topical anesthesia with regard to surgical outcomes, anxiety and pain. Methods: This randomized, crossover, controlled trial enrolled patients undergoing surgery for bilateral cataract under topical anesthesia at Cochin Hospital (Paris, France), from February to May 2021. Patients were randomly assigned to the non-fasting or fasting group for the first eye surgery and were switched to the other group for the second eye surgery. The primary endpoint was to compare the rate of anesthetist’s interventions during surgery. The secondary endpoints included intra-operative complications, duration of surgery, surgeon perception of surgical difficulty, anesthesia-related complications and anxiety and pain level. Results: 119 consecutive patients were included, with 60 of them being fasted first and non-fasted for the second eye surgery, while the other 59 were non-fasted first and fasted for the next surgery. The number of patients requiring sedation was significantly lower in the non-fasting group compared with the fasting group (1%; 95%IC [0-3.2] vs. 6%; 95%IC [2.9-8.9], P = 0.04). No anesthesia-related complications were observed. There was no difference in the number of intra-operative complications between the non-fasting and the fasting groups (respectively, 0 and 1; P = 1). Anxiety level and surgical pain were significantly lower in the non-fasting group compared to the fasting group (respectively, 2.3 ± 2.0 vs. 4.1 ± 2.4, P = 0.01 and 0.6 ± 0.6 vs. 2.6 ± 3.4, P = 0.003). The mean duration of surgery was significantly shorter in the non-fasting group compared with the fasting group (respectively, 16.0 ± 5.9 vs. 22.3 ± 6.1 min; P = 0.03). Conclusion: In conclusion pre-operatory non-fasting strategy provides a better patient experience with regards to preoperative anxiety and surgical pain. It allows to reduce operating times and is safe and well tolerated as regards the anaesthetic intervention.